An Inducible, Large-Intestine-Specific Transgenic Mouse Model for Colitis and Colitis-Induced Colon Cancer Research - Wang, Fa (Dig Dis Sci, 2015)
BACKGROUND: Animal models are an important tool to understand intestinal biology. Our lab previously generated C57BL/6-Tg(Car1-cre)5Flt transgenic mice (CAC) with large intestine specific Cre recombinase (Cre) expression as a model to study colon health. AIMS: To expand the utility of the CAC mouse model by determining the impact of chemically induced colitis on CAC transgene expression. METHODS: CAC mice were crossed to Rosa reporter mice (Rosa26R(flox/flox)) with a lox-STOP-lox signal controlling β-galactosidase (βgal) expression and then further crossed with Apc(CKO/CKO) mice in some experiments to delete Apc alleles (Apc(Δ580)) Initially, 8-wk-old CAC(Tg/WT);Rosa26R(flox/WT);Apc(Δ580/WT) mice were treated with dextran sulfate sodium (DSS) in drinking water (5 d, 0, 0.65%, 1.35%, or 2.0%). Colon tissue damage and βgal labelling were analyzed 10-d after stopping DSS. Next, 8-wk-old CAC(Tg/WT);Rosa26R(flox/flox) mice were treated with 0 or 1.35% DSS, and colonic β-gal labeling was assessed at 30-d post DSS treatment. Finally, 10-wk-old CAC(Tg/WT);Apc(Δ580/WT) mice were treated with DSS (0 or 2%) for 5 d and colonic tumors were analyzed at 20-wk. RESULTS: CAC(Tg/WT);Rosa26R(flox/WT);Apc(Δ580/WT) mice had a DSS dose-dependent increase in colon epithelial damage that correlated with increased epithelial β-gal labeling at 10-d (r(2) = 0.9, β = 0.75). The β-gal labeling in CAC(Tg/WT);Rosa26R(flox/flox) mice colon remained high at 30-d, especially in the crypts of the healed ulcer. DSS also increased colon tumor incidence and multiplicity in CAC(Tg/WT);Apc(Δ580/WT) mice. CONCLUSIONS: DSS-mediated epithelial damage induces a persistent, Cre-mediated recombination of floxed alleles in CAC mice. This enables the examination of gene function in colon epithelium during experimental colitis and colitis-induced colon cancer.